Baboon Model of Generalized Epilepsy: Continuous Intracranial Video-EEG Monitoring with Subdural Electrodes - Szabó, C. Ákos (2012)
The baboon provides a natural non-human primate model for photosensitive, generalized epilepsy. This study describes an implantation procedure for the placement of subdural grid and strip electrodes for continuous video-EEG monitoring in the epileptic baboon to evaluate the generation and propagation of ictal and interictal epileptic discharges. Subdural grid, strip and depth electrodes were implanted in six baboons, targeting brain regions that were activated in functional neuroimaging studies during photoparoxysmal responses. The baboons were monitored with continuous video-EEG monitoring for 2–21 (mean 9) days. Although the animals were tethered, the EEG signal was transmitted wirelessly to optimize their mobility. Spontaneous seizures, interictal epileptic discharges (IEDs), and responses to intermittent light stimulation (ILS) were assessed. Due to cortical injuries related to the electrode implantation and their displacement, the procedure was modified. Habitual myoclonic and generalized tonic-clonic seizures were recorded in three baboons, all associated with a generalized ictal discharge, but were triggered multiregionally, in the frontal, parietal and occipital cortices. IEDs were similarly expressed multiregionally, and responsible for triggering most generalized spike-and-wave discharges. Generalized photoparoxysmal responses were activated only in one baboon, while driving responses recorded in all three photosensitive baboons were 2.5 times the stimulus rate. In contrast to previous intracranial investigations in this model, generalized ictal and interictal epileptic discharges were triggered by parietal and occipital, in addition to the frontocentral cortices. Furthermore, targeted visual areas responded differently to ILS in photosensitive than nonphotosensitive baboons, but further studies are required before mechanisms can be implicated for ILS-induced activation of the epileptic networks.